2005
DOI: 10.2466/pr0.96.3c.1095-1112
|View full text |Cite
|
Sign up to set email alerts
|

Word Frequency Effect in False Memories

Abstract: Fuzzy Trace Theory argues that false memories arise from a weak verbatim memory along with strong encoding of the meaning (gist). The present study simultaneously investigated the effects of the strength of both the gist and the verbatim information on false memories. Exp. 1 was carried out to compare false memories for common and rare words in recall and recognition. In Exp. 2 a control for possible testing effects was added, and participants were given a recognition test with no preceding recall test. Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…To illustrate, five manipulations that increase R judgments for presented items are replacing word lists with picture lists (Wagner, Gabrieli, & Verfaellie, 1997), increasing the number of times a list is presented (Dewhurst & Hitch, 1997), replacing longer lists with shorter ones (Rajaram, 1993), replacing lists of high-frequency words with lists of low-frequency words (Guttentag & Carroll, 1997), and testing young adult subjects rather than older adults (Duarte, Graham, & Henson, 2010). When these manipulations have been implemented in false memory experiments, each has lowered false memory (Brainerd, Payne, Wright, & Reyna, 2003; Goz, 2005; Gallo & Roediger, 2003; Schacter et al, 1999; Sugrue & Hayne, 2006). …”
Section: Young Adulthood: the Dual-recollection Hypothesismentioning
confidence: 99%
“…To illustrate, five manipulations that increase R judgments for presented items are replacing word lists with picture lists (Wagner, Gabrieli, & Verfaellie, 1997), increasing the number of times a list is presented (Dewhurst & Hitch, 1997), replacing longer lists with shorter ones (Rajaram, 1993), replacing lists of high-frequency words with lists of low-frequency words (Guttentag & Carroll, 1997), and testing young adult subjects rather than older adults (Duarte, Graham, & Henson, 2010). When these manipulations have been implemented in false memory experiments, each has lowered false memory (Brainerd, Payne, Wright, & Reyna, 2003; Goz, 2005; Gallo & Roediger, 2003; Schacter et al, 1999; Sugrue & Hayne, 2006). …”
Section: Young Adulthood: the Dual-recollection Hypothesismentioning
confidence: 99%
“…To illustrate, consider five manipulations whose ability to increase true recollection is well documented: presenting a list of pictures rather than words, repeated presentation of a list, reducing the length of a list, decreasing the linguistic frequency of list words, and testing younger versus older adults. All of these manipulations have also been studied in false memory experiments, and each has been found to reduce false memory (see Brainerd, Payne, Wright, & Reyna, 2003; Duarte, Graham, & Henson, 2010; Gallo & Roediger, 2003; Goz, 2005; Schacter et al, 1999; Sugrue & Hayne, 2006). Now, consider five other manipulations whose ability to increase true recollection is also well documented: generating rather than reading a list, studying list items under longer rather than shorter exposure times, studying an emotionally valenced list rather a neutral one, studying a list under full rather than divided attention, and studying a list under deep rather than shallow encoding instructions.…”
Section: Complementary Effects Of True Recollection On False Memorymentioning
confidence: 99%
“…While found no effects in false recognition from word frequency, Anaki, Faran, Ben-Shalom, and Henik (2005) found that low-frequency lures have more false recognitions than do high-frequency lures. Göz (2005), on the other hand, found that high-frequency lures have higher rates of false recognition than do low-frequency lures. In the present study, we found no significant correlation between false recognition for each type of critical lure and word frequency.…”
Section: Resultsmentioning
confidence: 92%